Automatic Roof Prototype On Aviary With Telegram Based Monitoring - Muhammad Irsyad Hidayatullah; Indah Sulistiyowati; Dwi Hadidjaja Rasjid Saputra (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Aviary is a large cage that is designed to resemble the natural habitat of the flora and fauna contained therein. The purpose of making an aviary is as a breeding place for several flora and fauna within the scope of the community. Apart from that, some people build an aviary in their yard as a place to channel their hobbies. The success of aviary development has many supporting factors, one of which is weather conditions. Many aviaries out there do not have a protective roof so that the aviary experiences bad conditions when it rains, considering that Indonesia is a country with a tropical climate where rain can fall at any time. Based on these problems, this research was carried out by designing an automatic roof prototype that was placed on the aviary with a working system to detect the conditions that existed in the aviary and to protect the aviary from exposure to heat and excess rain. The prototype will detect the light intensity value and the value from the rain sensor reading, when it exceeds the specified value limit the tool will work and the roof will be closed. Contribution of this research The application of this prototype directly has a success rate of up to 90% as long as the components used can work optimally. The contribution to this research is the use of the Research and Development method as a research method and the use of telegram bots as a monitoring tool in this study.